(2x+1)(2x+3)=35

Simple and best practice solution for (2x+1)(2x+3)=35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+1)(2x+3)=35 equation:


Simplifying
(2x + 1)(2x + 3) = 35

Reorder the terms:
(1 + 2x)(2x + 3) = 35

Reorder the terms:
(1 + 2x)(3 + 2x) = 35

Multiply (1 + 2x) * (3 + 2x)
(1(3 + 2x) + 2x * (3 + 2x)) = 35
((3 * 1 + 2x * 1) + 2x * (3 + 2x)) = 35
((3 + 2x) + 2x * (3 + 2x)) = 35
(3 + 2x + (3 * 2x + 2x * 2x)) = 35
(3 + 2x + (6x + 4x2)) = 35

Combine like terms: 2x + 6x = 8x
(3 + 8x + 4x2) = 35

Solving
3 + 8x + 4x2 = 35

Solving for variable 'x'.

Reorder the terms:
3 + -35 + 8x + 4x2 = 35 + -35

Combine like terms: 3 + -35 = -32
-32 + 8x + 4x2 = 35 + -35

Combine like terms: 35 + -35 = 0
-32 + 8x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-8 + 2x + x2) = 0

Factor a trinomial.
4((-4 + -1x)(2 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {-4, 2}

See similar equations:

| m^3+m^2-16m+20=0 | | 8.3-14b=X | | (7x-6)=6+x | | 0=1+6x+x^2 | | x+iy=1 | | (8-2x)(12-2x)x=0 | | 3(s+1)+1=19 | | 9c-8=-5 | | -2-17g=-18g-20 | | 8(n-7)-2(4n+5)=5n-3+5n+7 | | (X-5)/62 | | 2+17d=11d-16 | | 4x-15=2x-17 | | (X-5)/6/ | | x^2-9=91 | | .10d+.25q=3.60 | | 6b+6=12 | | 4x-15=3x-17 | | 37=16t^2+484 | | -15.5r+19.61=8.3r-12.24+0.7 | | (4*x)-7=58-x | | x^2-12+36=12 | | 29x+3=28x+7 | | 5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5=50 | | 2/3x2.6= | | 3-6v=45 | | 6-5/6= | | -4+s=68 | | 18+7x=-3(5-5x)-7 | | (-5x^3y)*(-10x^4y^2)=0 | | y=20x^2-105x-90 | | 0.09xX=102.84 |

Equations solver categories